(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Beach ridges and barrier islands along the Nigerian coastline are a critical geomorphic unit which serve as foundation for several significant engineering structures, yet their geotechnical behavior remains unevenly characterized. This study synthesizes existing sedimentologic, geotechnical, and geophysical data to characterize the engineering properties of Nigerian beach‐ridge and barrier–island systems, with emphasis on the barrier–lagoon complex of Lagos, Brass, Bonny and Eket. The study identified hidden, shallow, incompetent, and highly compressible plastic clay/peat layers beneath the predominant seemingly stable sand, which can lead to significant consolidation settlement or building collapse. The near-surface sediments reveal poorly graded sands or silty sands, with high natural moisture content, low plasticity, moderate to high hydraulic conductivity, and decreasing relative density and relative compaction within the depth of significance to shallow foundation construction. Grain-size analyses from multiple barrier beaches indicate predominantly fine sands that are moderately to well sorted, reflecting moderately high wave-energy swash and backwash processes and indicating high susceptibility to coastal erosion. Integrated geophysical–geotechnical approaches have proven effective in mapping these contrasting strata and in estimating relative density and compactness, compressibility and settlement distribution and suitable foundation depths. This study further shows that a sandy top of thickness 3.5m can present an average safe bearing pressure for shallow foundation of 100kN/m2 and that satisfactory foundation performance may be expected, provided the bearing resistance of the soil at 3.5m depth is not less than 10% of the structural load placed on the surface. The combined evidence indicates that while Nigerian beach ridges and barrier islands often provide adequate near-surface materials for light to moderate structures, careful site-specific characterization is essential to account for underlying soft sediments, shoreline erosion, and associated geohazard risks.